Results and feedback from the British Dam Society 2020 year-end survey. Issue 2 (3rd June 2021) - Lockett, Stephen; Coombs, Rhys; Loughrey, Sarah
Abstract : In December 2020, the British Dam Society (BDS) conducted a year-end survey of both its individual and corporate members. The survey asked that members rate how much they agreed with a series of statements and were given the opportunity to submit additional comments. The survey contained 14 questions for individual members and three questions for corporate members. This paper presents the results of the survey along with feedback from the BDS Committee.